Penerapan Program Akselerasi Baca Kitab Kuning di Majelis Musyawarah Kutubuddiniyah (M2KD) PP. Mambaul Ulum Bata-Bata Ds. Panaan Kec. Palengaan Kab. Pamekasan - Behri, Mat (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2017)
An Efforts to improve the quality of education are always done conventionally or innovatively. To improve the quality of education required improvement of teaching and learning process. One of the efforts can be done with the implementation of a good acceleration program. So the learning could achieved effectively and efficiently. The purpose of this research are: (1) to know the background of the acceleration program, (2) to know the management of acceleration program implementation, (3) to know the problem of teacher and student in implementing the acceleration program. Research on acceleration program used qualitative approach, subject in this research is informant including teacher and student in M2KD PP. Mambaul Ulum Bata-Bata Pamekasan. data collected by observation, interviews, and documentation. This study yielded the findings. First, the background of the accelerated program is the difficulty of students in learning problems. Second, program management acceleration throught "kitab kuning" in M2KD PP. Mambaul Ulum Bata-Bata Pamekasan done at night with planning done by managers, participants, looked effective implementation and good output as well. Third, the obstacle faced by PP Mambaul Ulum Bata-Bata related by facilities in M2KD Mambaul Ulum Bata-Bata Pamekasan